SISTEM INFORMASI KAS KEUANGAN DESA PRIGELAN KECAMATAN PITURUH KABUPATEN PURWOREJO - Imam Tri Suryadin (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2018)
Angga Dwiyanto, "Financial Information System Cash Prigelan Village, District Pituruh, Purworejo", Final DIIIInformatics Engineering Program, under the guidance of Damar Eko Cahyono, ST, MM and Agus Dwi Atmoko, SE,M.M., Juli 2015, 66 pages + xix + attachments. The purpose of this research is to design information systems of financial cash Prigelan villages, districts Pituruh,Purworejo district to address the village's financial cash management processes in order to more quickly and accurately. The research methodology used by the authors are iterative methods. Which had a few stages of the first phase of thesurvey system, the second stage of the analysis system, the third stage of system design by using models that describe thedata flow system, and ERD identifies the user interface and data interface design, the fourth stage of the manufacturingsystem Borland Delphi 7.0 and using MySQL, the fifth stage of the implementation, the sixth stage of life cyclemaintenance of the system so that the system remains useful, productive and optimal. The analysis and design of this system is expected to facilitate preangkat village, which especially in the treasurer inmanaging the financial treasury village.